Mutational analysis of the DNA mismatch repair genes, hMLH1 and hMSH2, in South African colorectal cancer patients - Van Rensburg, Elizabeth J. (University of Pretoria, 2013)
Dissertation (MSc (Human Genetics))--University of Pretoria, 2005.